2008
DOI: 10.1037/0012-1649.44.1.139
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of classroom situational dimensions of emotional and behavioral adjustment and cognitive and social outcomes for Head Start children.

Abstract: This study employed a developmental-ecological approach to investigate the relationship across the school year between early problems in preschool classroom situations and a comprehensive set of readiness competencies for urban, low-income children. Study I identified three reliable and unique underlying classroom situational dimensions where behavior problems occurred: Structured Learning, Peer Interaction, and Teacher Interaction situations. Boys and younger children evidenced more problematic behavior acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 89 publications
(127 reference statements)
3
57
0
3
Order By: Relevance
“…As with the prior study, the ASPI was used as a measure of assessment. Results conclude that children who have factors impacting their social development (biological, psychological or environmental) and who displayed behavioural difficulties had a harder time adapting socially (Bulotsky-Shearer et al, 2008). Therefore, not only does the presence of early behavioral issues indicate the potential continuation of these behaviors, the research also indicates that ecological factors such as parental income play an important role as well.…”
Section: According To the United States Department Of Health And Humamentioning
confidence: 85%
See 1 more Smart Citation
“…As with the prior study, the ASPI was used as a measure of assessment. Results conclude that children who have factors impacting their social development (biological, psychological or environmental) and who displayed behavioural difficulties had a harder time adapting socially (Bulotsky-Shearer et al, 2008). Therefore, not only does the presence of early behavioral issues indicate the potential continuation of these behaviors, the research also indicates that ecological factors such as parental income play an important role as well.…”
Section: According To the United States Department Of Health And Humamentioning
confidence: 85%
“…Finally, and importantly, children who showed socially disruptive behavior initially were shown to be less engaged, cooperative and attentive later in the study (Fantuzzo et al, 2005). In a later study conducted by Bulotsky-Shearer, Fantuzzo & McDermott (2008) the investigation of identifying situational dimensions of behavior over the course of the school year as well as looking at the many dimensions of goal learning outcomes. Again, a population of Head Start students was used, but the sample size was considerably larger than the Fantuzzo et al study.…”
Section: According To the United States Department Of Health And Humamentioning
confidence: 99%
“…Om interventies in de klas of op de groep zo doelgericht mogelijk uit te voeren is onderzoek nodig dat gebruik maakt van meetinstrumenten die gedragsproblemen zoals die zich in standaard leersituaties (kunnen) voordoen nauwkeurig identificeren en die tevens praktisch toepasbare kennis opleveren voor de professionals die met de jonge kinderen werken (Bulotsky-Shearer, Fantuzzo, & McDermott, 2008;Klein & Knitzer, 2007). De vraag is echter hoe gedragsproblemen kunnen worden geïdentificeerd die variabelen als ontluikende geletterdheid en taalvaardigheid -essentiële onderdelen van elk VVE-programma -het sterkst negatief beïnvloeden.…”
Section: Het Belang Van Gedragsmatige Aspecten Van Schoolrijpheidunclassified
“…Gender differences in children's skills and capabilities are often evident at school entry (Bulotsky-Shearer, Fantuzzo, & McDermott, 2008), particularly in regards socioemotional development. Several studies have identified gender differences in aggression (Hood, 1996;Zimmer-Gembeck et al, 2005), with boys being more aggressive than girls, and prosocial behaviour (Romano et al, 2005;Zimmer-Gembeck et al, 2005), with girls displaying more prosocial behaviours than boys.…”
Section: Familial Factors and School Readinessmentioning
confidence: 99%